Characterizing Highly Frequent Users of a Large Canadian Urban Emergency Department - Kim, Julie; Kwok, Edmund; Cook, Olivia; Calder, Lisa (Université d'Ottawa | University of Ottawa, 2018)
Highly frequent users (HFU) of the emergency department (ED) are a poorly defined population. This study describes patient and visit characteristics for Canadian ED HFU and patient subgroups with mental illness, substance misuse, or ≥ 30 yearly ED visits.
Keywords: Abdominal Pain; Adolescent; Adult; Aged; Aged, 80 and over; Alcoholic Intoxication; Emergency Service, Hospital; Female; Humans; Male; Middle Aged; Musculoskeletal Pain; Ontario; Retrospective Studies; Young Adult; Triage